PENGARUH PROFITABILITAS, SOLVABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman dan Kosmetik dan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020) - Rossalita, Eliya Ayu; Gantino, Rilla (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to analyze the Effect of Profitability, Solvency and Company Size on Company Value Empirical Study on Food and Beverage and Cosmetics and Household Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2016-2020 Period. Profitability is measured using Return on Assets (ROA) which uses the formula EBIT (Earnings Before Interest and Tax) divided by total assets. Solvency is proxied by the Debt to Equity Ratio (DER) measured using total debt divided by total capital. And Company Size is proxied by Size measured using the natural logarithm of total sales. While the Company Value in this study is proxied by Price to Book Value (PBV) with the stock price formula divided by the book value per share. The method used in this study is a saturated sample technique where all members of the population are used as samples. Using several predetermined criteria, this study amounted to 18 food and beverage companies and 5 cosmetic and household companies so that the total sample was 23 companies listed on the Indonesia Stock Exchange in 2016-2020. The type of data used in this study is secondary data sourced from financial statements and annual reports. The data analysis method used is multiple linear regression analysis. The results of hypothesis testing show that simultaneously Profitability, Solvency, and Company Size have a significant effect on Company Value. Partially, profitability has a positive and significant effect on Company Value in food and beverage sub-sector companies and cosmetics and household sub-sector companies. Solvency does not have a significant effect on Company Value in food and beverage sub-sector companies, while Solvency has a positive and significant effect on Company Value in cosmetics and household sub-sector companies. Company Size has a positive and significant effect on Company Value in food and beverage sub-sector companies, while Company Size has a negative and significant effect on Company Value in cosmetics and household sub-sector companies.